Varifocal metalens using tunable and ultralow-loss dielectrics - Wang, M; Lee, JS; Aggarwal, S; Farmakidis, N; He, Y; Cheng, T; Bhaskaran, H (Wiley, 2023)
The field of flat optics that uses nanostructured, so-called metasurfaces, has seen remarkable progress over the last decade. Chalcogenide phase-change materials (PCMs) offer a promising platform for realizing reconfigurable metasurfaces, as their optical properties can be reversibly tuned. Yet, demonstrations of phase-change metalenses to date have employed material compositions such as Ge2Sb2Te5, which show high absorption in the visible to near-IR wavelengths particularly in their crystalline state, limiting the applicability. Here, by using a low-loss PCM Sb2Se3, for the first time, active polarization-insensitive phase-change metalenses at near-IR wavelengths with comparable efficiencies in both material states are shown. An active metalens with a tunable focusing intensity of 95% and a focusing efficiency of 23% is demonstrated. A varifocal metalens is then demonstrated with a tunable focal length from 41 to 123 µm with comparable focusing efficiency (5.7% and 3%). The ultralow-loss nature of the material introduces exciting new possibilities for optical communications, multi-depth imaging, beam steering, optical routing, and holography.